Edukasi Menabung Sejak Dini Kepada Siswa SDN Narawita 01 dan 02 - Fauzi, Yasir Muharram; Fadhillahanne; Kusnadi, Ria Riyani; Nur Huda, Muhammad Fauzi (Ma'soem University, 2025)
This research is motivated by the lack of early savings culture in students of SDN Narawita 01 and 02 in saving, this is important because it is to instill good habits from an early age, form character and healthy financial habits in children. This community service program aims to provide education about the importance of saving to grade 1 elementary school students at SDN Narawita 01 and 02. The method used in this community service is the PAR (Participatory Action Research) method. PAR was chosen because it allows active community participation in all stages of the research, from identifying problems to implementing actions. The results of this service show that students begin to understand the importance of saving and show interest in practicing the habit. They also begin to understand how saving can help them achieve small goals in their lives, such as buying toys or school supplies. The meaning of the results of this service is that by starting savings education from an early age, children can develop positive financial habits, which will benefit their lives in the future. The importance of the results of this service lies in its contribution to forming a generation that is wiser in managing personal finances, which can ultimately contribute to the economic welfare of families and society as a whole.